The correlation of homemaking education and distributive education for girls in Montana - Stewart, Harryet H., author; Sackett, Everett B., advisor; Williamson, Maude, advisor; Sackett, Everett B., committee member; Williamson, Maude, committee member; Thompson, Hazel E., committee member; Burnham, Helen A., committee member; Holman, Mary V., committee member (Colorado State University. Libraries, 1944)
To view the abstract, please see the full text of the document.
Keywords: Home economics -- Study and teaching; Home economics -- Montana; Distributive education